Simulation of burial history, thermal evolution history, and hydrocarbon generation history of the Upper Cretaceous Yogou Formation source rocks in the Termit Basin - Tao Wang; Yang Wang; Shengqiang Yuan; Fengjun Mao; Jiguo Liu; Xiaowen Guo; Rui Yang (地质科技通报, 2023)
Objective The Yogou Formation source rock is an important Late Cretaceous source rock series in Termit Basin, Niger. Due to the lack of systematic research on the burial history, thermal evolution history, and hydrocarbon generation history of this set of strata, the understanding of oil and gas accumulation rules in this area is restricted. Methods In this paper, the thermal evolution history of the Yogou Formation source rocks in Termit Basin is restored by using the hydrocarbon generation dynamics model in BasinMod basin simulation software, combined with drilling wells, two-dimensional seismic profiles, and geochemical data. The thermal evolution characteristics of source rocks in different areas and their matching relationship with hydrocarbon accumulation are analysed, which provides important evidence for the next exploration of the Termit Basin. Results The results show that the heat flow value of Termit Basin has obvious two-stage evolution characteristics. The initial heat flow value is low and reaches maximum values in the Late Palaeogene (ranging from 64.3 to 69.2 mW/m2). Since the Neogene, the thermal state of the basin has been characterized by continuous cooling, and the current heat flow value is between 60.7 and 67.4 mW/m2. The hydrocarbon generation of the top Yogou Formation began at 55 Ma (Ro=0.5%), and the main hydrocarbon generation window (Ro=1.0%) started at 35 Ma and reached a high maturity level (Ro=1.3%) at 27.5 Ma. Two stages of hydrocarbon generation are found in the source rocks of the Yogou Formation; in particular, the Late Cretaceous (70-60 Ma) hydrocarbon generation stage mainly exists in the deep area depression of the basin, while the Palaeogene (40-20 Ma) is the main hydrocarbon generation stage of the whole basin. Compared to different tectonic belts show that the source rocks of the Dinga Depression are characterized by high maturity, earlier hydrocarbon generation, and stronger hydrocarbon generation, which are beneficial for providing sufficient hydrocarbons. The strong activity of the Palaeogene faults led to the migration and accumulation of oil and gas generated by the bottom source rocks into the Palaeogene reservoirs. Conclusion The research results can provide a basis for the evaluation of the hydrocarbon generation potential of source rocks in the Termit basin and provide theoretical guidance for oil and gas exploration in the basin.